Ask Experts & Get Answers to Your Questions - ASAP

Hi there,

x2-5x+6=0 x = 2 or 3solve for y 2x-y=3

y = 2x-3xsquared=7x

x = 0 or 77/x-1/x-3=9/xsquared-3x x = 5

factor completely 18asquaredb+36absquared

18a^2b + 36ab^2

= 18ab(a+2b)write fraction in simplest form 3xsquared+11x-4/ 2xsquared+11x+12

3x-1 / 2x+3

That's 3x-1 over 2x+3

simplify complex fraction 3+1/x/ 3-1/x

3x+1 / 3x-1

That's 3x+1 over 3x-1

Let me know if you have any questions or need work shown. If you're set, thanks for accepting.

Scott